Community-acquired pneumonia in Chile: the clinical relevance in the detection of viruses and atypical bacteria. Issue 11 (19th June 2013) - Luchsinger, Vivian; Ruiz, Mauricio; Zunino, Enna; Martínez, María Angélica; Machado, Clarisse; Piedra, Pedro A; Fasce, Rodrigo; Ulloa, María Teresa; Fink, Maria Cristina; Lara, Pamela; Gebauer, Mónica; Chávez, Fernando; et al.
Abstract : Background: Adult community-acquired pneumonia (CAP) is a relevant worldwide cause of morbidity and mortality, however the aetiology often remains uncertain and the therapy is empirical. We applied conventional and molecular diagnostics to identify viruses and atypical bacteria associated with CAP in Chile. Methods: We used sputum and blood cultures, IgG/IgM serology and molecular diagnostic techniques (PCR, reverse transcriptase PCR) for detection of classical and atypical bacteria ( Mycoplasma pneumoniae, Chlamydia pneumoniae, Legionella pneumoniae ) and respiratory viruses (adenovirus, respiratory syncytial virus (RSV), human metapneumovirus, influenza virus, parainfluenzavirus, rhinovirus, coronavirus) in adults >18 years old presenting with CAP in Santiago from February 2005 to September 2007. Severity was qualified at admission by Fine's pneumonia severity index. Results: Overall detection in 356 enrolled adults were 92 (26%) cases of a single bacterial pathogen, 80 (22%) cases of a single viral pathogen, 60 (17%) cases with mixed bacterial and viral infection and 124 (35%) cases with no identified pathogen. Streptococcus pneumoniae and RSV were the most common bacterial and viral pathogens identified. Infectious agent detection by PCR provided greater sensitivity than conventional techniques. To our surprise, no relationship was observed between clinical severity and sole or coinfections. Conclusions: The use of molecular diagnostics expanded the detection of viruses and atypical bacteria in adults with CAP, as unique or coinfections. Clinical severity and outcome were independent of the aetiological agents detected.